Thursday

October 2, 2014

October 2, 2014

Posted by **hurry! nick** on Monday, May 6, 2013 at 8:05am.

- hurry! math -
**Steve**, Monday, May 6, 2013 at 10:43am125^x-2 = 125^2 * 125^x-4

125^x-3 = 125 * 125^x-4

so, what we have is

125^x-4 (125^2 - 125) = 125^x-4

125^2 - 125 = 1

No solution

Evidently I misunderstood the notation. If you meant

125^x - 2 + 125^x - 3 = 125^x - 4

125^x = 1

x = 0

**Answer this Question**

**Related Questions**

statistics - Use the list and calculation method to answer the following ...

math - which of the following expressions shows the equation to use in finding ...

math - which of the following expressions shows the equation to use in the ...

mathematics - which of the following expressions shows the equation to use in ...

math - which of the following expressions shows the equation to use in finding ...

math - if 3M/2N=0.125, what is the value of N in terms of M? This is the workout...

chemistry - is this the right anser? for this problem please let me know thanks ...

chemistry/please double check - Hi, I just need to know if I finally got this ...

math 11 - simplify (make the radicand as small as possible) 125^-2/3 =125^3/2 =...

Math-Ms. Sue - The number of dry cleaning orders picked up at Sunny Fresh Dry ...